Cochlear Enhancement May Precede Cochlear Obliteration After Vestibular Schwannoma Excision. Issue 2 (February 2020) - Erbele, Isaac D.; Miller, Laura S.; Mankekar, Gauri; Morel, Christian E.; Anderson, Dwayne T.; Son, Leslie S.; Arriaga, Moises A.
Abstract : Objective: Cochlear obliteration after vestibular schwannoma excision has been noted, with implications on cochlear implantation. Early postoperative cochlear enhancement with gadolinium on magnetic resonance imaging (MRI) has also been observed. Timing of enhancement and association with obliteration is described here. Study Design: Retrospective case review. Setting: Tertiary referral center, ambulatory. Patients: Patients receiving vestibular schwannoma excision surgery by the senior author performed at one institution between January 2015 and July 2017 with postoperative MRIs Intervention: Diagnostic. Main Outcome Measure(s): The imaging characteristics on postoperative MRIs examined were loss of fluid signal on postoperative T2 images and cochlear enhancement on gadolinium enhanced T1 images. In the patients receiving labyrinthine sparing procedures, presence of postoperative hearing was evaluated. Results: Of the 42 patients evaluated, 24 received the translabyrinthine approach and 18 received a labyrinth sparing surgery. Twenty-nine had evidence of cochlear enhancement on T1 with gadolinium contrast, and 27 had evidence of cochlear obliteration on T2 images. The odds ratio of patients with cochlear enhancement having obliteration was 30.0:1 ( p  < 0.0001). Intense cochlear enhancement (n = 21) appeared a median of 163 days after surgery, and complete or near complete obliteration (n = 18) appeared a median of 480 days after surgery, a statistically significant difference ( p  < 0.001). Within the labyrinth sparing group, there was no statistically significant association between hearing loss and cochlear obliteration or enhancement. Conclusions: Cochlear enhancement is correlated with cochlear obliteration and may precede it.